2017
DOI: 10.1016/j.jse.2016.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and familial predisposition to rotator cuff disease: a systematic review

Abstract: Background Rotator cuff disease is a common disorder leading to shoulder pain and loss of function. Its etiology in atraumatic cases is uncertain and likely extends beyond repetitive micro-trauma or overuse. Our objective was to determine whether there is a genetic or familial predisposition to rotator cuff disease. Methods A literature search of PubMed and EMBASE databases identified 251 citations. After reviewing the titles, abstracts, and full articles, seven met our inclusion/exclusion criteria. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 36 publications
0
35
0
6
Order By: Relevance
“…Age, female gender, smoking, dyslipidemia, and diabetes are well‐documented risk factors. Recently, increasing evidence suggests that a RCT is a multifactorial process in which genetic factors, in addition to extrinsic/environmental factors, contribute to disease susceptibility . Single‐nucleotide polymorphisms (SNPs) are common genetic variants (>1% of the population) that can lead to qualitative or quantitative variations in RNA or protein products, but the variations generally have smaller phenotypic effects than mutations.…”
mentioning
confidence: 99%
“…Age, female gender, smoking, dyslipidemia, and diabetes are well‐documented risk factors. Recently, increasing evidence suggests that a RCT is a multifactorial process in which genetic factors, in addition to extrinsic/environmental factors, contribute to disease susceptibility . Single‐nucleotide polymorphisms (SNPs) are common genetic variants (>1% of the population) that can lead to qualitative or quantitative variations in RNA or protein products, but the variations generally have smaller phenotypic effects than mutations.…”
mentioning
confidence: 99%
“…Genetics also seems to influence the occurrence of cuff tears 59 . Harvie et al found a more than doubled risk of full thickness tear in siblings in a case-control study, comparing siblings and spouses for patients with fullthickness tears 116 .…”
Section: Prevalence and Predisposing Factors For Rotator Cuff Tearmentioning
confidence: 99%
“…The high frequency of bilateral pathology, and the strong correlation between the two shoulders, indicate that a trauma, or repetitive overuse of a dominant shoulder, cannot be the only etiologic factors and that systemic factors must have a significant role for the development of many cuff tears. These systemic factors may be both genetic 59 and acquired 221 and affect tendon homeostasis. Patients who have an increased amount of predisposing factors will perhaps develop a bilateral disease with initial involvement of the dominant shoulder and a subsequent involvement of the contralateral shoulder.…”
Section: The Contralateral Cuff Tearmentioning
confidence: 99%
“…This study was included in the systematic review conducted by Dabija et al [23], which includes the study by Harvie et al [24], concluding that siblings of patients diagnosed with RCTs were twice as likely to develop complete RCTs. In addition, they identified single-nucleotide polymorphisms (SNPs) associated with RCTs, indicating the future risk for development of RCTs to enable prophylactic rehabilitation techniques and to avoid the development of symptomatic RCTs [23].…”
Section: Family Historymentioning
confidence: 99%